Attitudes towards patient safety culture among pediatric nurses at government tertiary hospital in Vietnam - Thi Ngoc, Nguyen Han; Thi Yen, Nguyen Nhi; Thi My, Nguyen Duyen; Nguyen, Tuan Van; Wantonoro; Manahan, Lydia T.; Yang, Hsiu-Ling (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2024)
Pediatric patients are vulnerable to medication errors. Nurses have essential roles in patient safety and their quality of care. Therefore, nurses' attitudes regarding safety culture help nurses gain a profound insight into patient safety problems as well as potential solutions to cope with them. Motivating nursing professionals to understand safety culture and how they act about patient safety is one of the first steps to improving patient safety in healthcare institutions. This study aims to investigate attitudes towards patient safety culture among pediatric nurses and related factors. A cross-sectional descriptive correlational design was used with a sample size of 105 pediatric nurses at a selected government hospital in the Mekong Delta, Vietnam. Nurses’ attitudes towards patient safety culture were examined using a 4-likert questionnaire including 30 items divided into six subscales. Data analysis was performed in SPSS Version 26.0 using descriptive statistics and analysis of variance (ANOVA). The study findings showed that the overall mean score of attitude towards patient safety culture was 3.30 (SD = 0.45). Among subscales of attitudes, teamwork climate had the lowest mean scores. There were statistically significant associations between the level of education, experience, and nurses’ attitudes. According to the results, nurses’ attitudes regarding patient safety culture were good. However, there were some aspects that should be enhanced. It is strongly recommended that specific training interventions be performed to enhance the teamwork climate in the hospital.